A Robotic Brain Scheme: Proposal Originated by a Modular Robotic Control - J. Negrete-Martínez (Applied Bionics and Biomechanics)
A robot brain scheme has been implemented, based on and controlled by analog circuits and micro-controllers. The modules have been classified as: (a) world signal processing, (b) world signal relevance assessing, (c) pre-motor decisions, (d) motor behavior, and (e) planning and sequencing motor behaviors. There are two types of pre-motor processing: main and world signal tracking. Motor behavior includes all the final motion units. Each of these five classes roughly corresponds to areas in a vertebrate’s brain and proved to be an effective robotic brain scheme as they assist in the development of greater complexity in robotic brains and a means to compare different implementations. The scheme stresses the importance of motor behavior modules fed by pre-motor decision modules. The pre-motor decision modules aim the movement while the motor behavior module creates the behavior. Finally, the planning and sequencing modules are imperative implementations in a robotic brain.